Frequência e perfil de gestantes com toxoplasmose em uma unidade de saúde de Matão - SP - Albaricci, Camila Biazoni [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Congenital toxoplasmosis is a serious public health case, for it causes irreversible damage to the embryo/fetus, which may cause its death. The identification and the care to pregnant women with suspect acute toxoplasmosis (IgM+) is performed in prenatal monitoring. This study aimed to measure the incidence and know the profile of positive pregnant women for toxoplasmosis in a Basic Health Unit (BHU) in Matão - SP, between the years 2011 to 2013. This is a retrospective descriptive study, from the medical records of pregnant women attended. The project was approved by the Municipal Departament of Health and BHU was chosen along the Municipal Epidemiological Surveillance. From 2011 to 2013, 189 women began prenatal care in the unit, an annual median of 71(±26.91), of which 17 (8.99%) were positive for the serological test indicative of acute phase (IgM+). The distribution over the trial period was: four cases in 2011, twelve cases in 2012 and one in 2013. Pregnant women IgM positive for toxoplasmosis attend by BHU were: age 24(±5.47) years; color: equally distributed among white, black and brown; as the number of pregnancies: multiparous (2±0.97), most of them with a cesarean delivery as obstetric history and possessed no other risk factors associated with pregnancy (94.12%); gave entrance at BHU with 13.65(±7.35) weeks of gestation and had a median of 5(±2.36) consultation on their prenatal care. The examination for toxoplasmosis was requested as recommended by the Health Ministry (HM) and the medication prescribed was Roxamicina® - spiramycin, as soon as the test results (IgM+) arrived. Of the 17 pregnant women, only 10 completed the pre-natal at BHU - attendance at the postpartum consult (58.8%). Of these, the deliveries were vaginal (55.55%), made preterm with 36.5 weeks of gestation at the Municipal Hospital. The babies were born alive (100%) with the weight of 2.68(±0.77) Kg and required special care hospital scope. From the ...

A toxoplasmose congênita é um caso sério de saúde pública, pois acarreta danos irreversíveis ao embrião/feto, podendo ocasionar o seu óbito. A identificação e o cuidado das gestantes com suspeita de toxoplasmose aguda (IgM+) são realizados no acompanhamento pré-natal. Este trabalho teve por objetivo medir a frequência e conhecer o perfil das gestantes positivas para toxoplasmose em uma unidade básica de saúde (UBS) em Matão - SP, entre os anos de 2011 a 2013. Trata-se de um estudo descritivo retrospectivo, a partir dos prontuários das gestantes atendidas. O projeto foi aprovado pela Secretaria Municipal de Saúde e a UBS foi escolhida juntamente à Vigilância Epidemiológica do município. De 2011 a 2013, 189 mulheres iniciaram o pré-natal na unidade, uma média anual de 63(±26,91), das quais 17 (8,99%) apresentaram positividade para o teste sorológico indicativo de fase aguda (IgM+). A distribuição ao longo do período avaliado foi: quatro casos em 2011, 12 casos em 2012 e um em 2013. As características das gestantes IgM positivas para toxoplasmose atendidas pela UBS foram: idade 24(±5,47) anos; cor: igualmente distribuídas entre brancas, pardas e pretas; quanto ao número de gestações: multíparas (2±0,97); a maior parte delas com um parto cesárea como antecedente obstétrico (47,06) e não possuíram outros fatores de risco associados à gestação (94,12%); deram entrada na UBS com 13,65(±7,35) semanas de gestação e tiveram uma mediana de 5 consultas pré-natais. O exame para toxoplasmose foi solicitado como preconiza o Ministério da Saúde (MS) e a medicação prescrita foi Roxamicina® - espiramicina, assim que se obteve o resultado do exame (IgM+). Das 17 gestantes, apenas 10 finalizaram o pré-natal na UBS - comparecimento na consulta puerperal (58,8%). Dessas, os partos foram vaginais (55,55%), realizados prematuramente com 36,5 semanas de gestação, no Hospital Municipal. Os bebês nasceram vivos ...
Keywords: Toxoplasmose; Saúde pública; Mulheres grávidas; Gravidez; Toxoplasmosis